The Relationship of Digital Marketing Advertising Strategies with Television Advertising Jingles in Increasing Brand Awareness on Shopee - Fadhiilah, Muhammad Alwan; Putri, Kinkin Yuliaty Subarsa; Sary, Marisa Puspita (Journal of Digital Marketing and Communication, 2025)
Television is an electronic media that is used for information and entertainment media. Currently, television is used as a promotional medium for brand advertisements, because the audience is very wide, all groups watch television, and the advertisements are short but clear in meaning. Shopee is one of the big brands that uses advertising services on television. This research was created with the aim of finding out the relationship of digital marketing advertising strategies with television advertising jingles in increasing brand awareness on Shopee. The research method used in this writing is quantitative descriptive research with a research sample of 56 respondents. Primary data was obtained by distributing questionnaires to respondents boardly. The research results shot that the digital marketing advertising strategy of television advertising jingles in increasing brand awareness on Shopee can be said to be effective and relevant because the average respondent agrees with it.